The acoustic wave generation by a thin layer with variable temperature - DYBA, Roman; ŻÓŁTOGÓRSKI, Bronisław (Archives of Acoustics, 1987)
This study considers the problem of the thermal sound generation in the air by an unmoving solid body with a time-variable temperature. Applying the linear relations between the thermal energy stream supplied to a thin layer of a solid body in touch with a gaseous medium and an energy stream of the acoustic wave, and then taking advantage of electrothermo-acoustic analogies, the phenomena of the energy transport were represented in the form of an equivalent linear electric circuit with lumped constants. On the basis of the equivalent circuit, both the properties of the considered thermal source of the acoustic wave were investigated and the problem of thermo-acoustic cooling of the solid body was discussed. It was shown that, in view of the low efficiency of the temperature—pressure conversion, it is necessary to generate large layer temperature changes to obtain the mean values of sound intensity, whereas the maximum of the modulus of the transmittance function of the source occurs even for very thin layers. It was also shown that in the course of cooling of thin layers the amounts of energy: that carried by the acoustic wave and that supplied to the environment as a result of external conduction arc comparable, so that in the energy balance of a thin layer with varying temperature, it is necessary to take into account the two factors which bring about an energy loss.